Combining experimental and numerical analysis to estimate stress fields along the surface crack front - A.S. Chernyatin; Yu.G. Matvienko; I.A. Razumovsky (Fracture and Structural Integrity)
Combining experimental and computational method for determination of the singular and the nonsingular stress terms along the front of the 3D surface crack is proposed. Evaluation of the terms is based on comprehensive comparison between deformation responses (for measurement points on the surface) obtained experimentally and from numerical solutions of the corresponding boundary problem of solid mechanics. The proposed approach allows carrying out an adequate and a comprehensive assessment of stress fields in the vicinity of the surface crack front.